Strategic Planning of IT/IS Using Ward and Peppard (PT Wahid Bangun Semesta Yogyakarta) - Pratiwi, Inge Dwi (Jurusan Informatika, 2025)
Purpose: This research aims to design an IS/IT strategy for PT Wahid Bangun Semesta to propose prioritized information systems that align with the company's existing challenges and to provide guidelines for application development. Design/methodology/approach: This study focuses on designing an IS/IT strategy using the Ward and Peppard methodology. Findings/result: Based on the findings, PT Wahid Bangun Semesta Yogyakarta is advised to implement an integrated information system to support operations and enhance competitiveness. Fingerprint systems are recommended to reduce attendance misuse. The application portfolio is designed to strengthen business processes according to identified needs. The IT strategy includes LAN and wireless networks at the head office, as well as USB modems and web-based applications at branch offices for flexible information access. Establishing an IT division is also recommended for more focused management, enabling IS/IT investments to positively contribute to company growth. Originality/value/state of the art: This study designs an IS/IT strategy for PT Wahid Bangun Semesta Yogyakarta to enhance operations and competitiveness through integrated information solutions. Proposed solutions include implementing an Integrated Information System, a fingerprint machine to prevent attendance misuse, LAN and wireless networks at the head office, broadband access at branch offices, and web-based applications.Establishing an IT division is recommended to manage IS/IT resources and ensure successful investments that support the company’s growth.